Reflections on the Aftermath of the Arab Spring - Jay Willoughby (International Institute of Islamic Thought, 2015)
On November 18, 2014, Datuk Seri Anwar Ibrahim, founder and board member, IIIT; leader of the Malaysian opposition; and former deputy prime minister of Malaysia, shared his “Reflections on the Aftermath of the Arab Spring” with the general public at the IIIT headquarters in Herndon, VA. He opened with “O you who believe! Obey Allah and obey the Apostle and those in authority from among you” (Q. 4:59), which he considers one of the Qur’an’s “most used and abused verses.” In addition to being used to support democracy, it is abused by many others to demand the masses’ support for dictators, authoritarian, and military junta rule regardless of how they are treated. This verse also highlights an issue that has rocked the Arab world ever since December 17, 2010, when Tunisian street vendor Mohamed Bouazizi set himself on fire to protest the continued abuse and harassment inflicted upon him by the Tunisian police force: the issue of governmental legitimacy, which is a problem in both the West and the Muslim world. Anwar stated that the government must represent a majority consensus, respect some process (e.g., democracy), and allow people the freedom of expression so that they can express their support, disgust, or opposition. The Arabs’ demand for legitimate governance has been on the mind of IIIT as well, for its leaders have spent the last decade addressing this concern from the point of view of the maqāṣid. Anwar traced this concern back to a long-ago meeting when several of the IIIT founders were discussing why there was no Muslim equivalent of the “Western canon,” the “Great Books,” a “great intellectual tradition.” This was the start of an ongoing process to fill this gap in contemporary Muslim literature. The outbreak of Arab Spring clearly revealed that there is still a need to deal with ethics in governance, for lasting reform can only be actualized in the form of systems. The ongoing abuse, corruption, repression, and brutality inflicted upon the people by their own leaders is, according to him, something ...